(untitled) (Global Journal of Medical Research, 2017)
How can we prevent premature leutinization in our IVF cycles? To help find the solution a study designed with specific exclusion criteria in an assisted reproductive centre of a tertiary care hospital was designed. In a period of 2 years 100 patients were followed up prospectively. GnRH antagonist protocol was implemented for all recruits because of shorter duration of treatment and as it prevented hyperstimulation. Specific criteria was chosen for GnRH anatagonist initiation. Serum Progesterone measurements were used to predict premature leutinization. Electro-chemiluminiscence Immunoassay using COBAS 6000 used for the measurements. Three different groups analysed in above cohort and we concluded that despite of progesterone rise pregnancy outcome was unaffected. Why is the question answered in discussion.